2017
DOI: 10.1002/ajh.24933
|View full text |Cite
|
Sign up to set email alerts
|

Improved prognosis with additional medium‐dose VP16 to CY/TBI in allogeneic transplantation for high risk ALL in adults

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) with the conventional cyclophosphamide and total body irradiation (CY/TBI) regimen is an essential therapeutic strategy for acute lymphoblastic leukemia (ALL) in adults. Medium-dose etoposide (VP16, 30-40 mg/kg) can be added to intensify this CY/TBI regimen and reduce relapse; however, differences in prognosis between the VP16/CY/TBI and CY/TBI regimens have not yet been fully analyzed. We conducted a retrospective cohort study using a Japanese transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Furthermore, according to the study by Marks et al [43], patients treated with alloHSCT in CR2 benefited from TBI dose ≥13 Gy as compared to <13 Gy, in terms of reduced risk of relapse and improved LFS. The Japanese group performed a retrospective study comparing 1178 ALL patients treated in first or subsequent CR with Cy/TBI and 376 ALL patients receiving Cy/TBI in combination with intermediate doses of etoposide (VP16, 30-40 mg/kg) [45]. The latter was associated with decreased risk of relapse (HR = 0.75, p = 0.05) and improved LFS (HR = 0.76, p = 0.01).…”
Section: Conditioningmentioning
confidence: 99%
“…Furthermore, according to the study by Marks et al [43], patients treated with alloHSCT in CR2 benefited from TBI dose ≥13 Gy as compared to <13 Gy, in terms of reduced risk of relapse and improved LFS. The Japanese group performed a retrospective study comparing 1178 ALL patients treated in first or subsequent CR with Cy/TBI and 376 ALL patients receiving Cy/TBI in combination with intermediate doses of etoposide (VP16, 30-40 mg/kg) [45]. The latter was associated with decreased risk of relapse (HR = 0.75, p = 0.05) and improved LFS (HR = 0.76, p = 0.01).…”
Section: Conditioningmentioning
confidence: 99%
“…In this study, two of the three patients who received intensified conditioning developed SOS. However, previous reports have shown that the addition of cytarabine or etoposide does not increase complication risk [ 16–19 ]. In fact, regimen-related toxicities other than SOS for these three patients were not serious and were comparable to the toxicities of the other seven patients.…”
Section: Discussionmentioning
confidence: 99%
“…The standard conditioning regimen consisted of cyclophosphamide (CY, 60 mg/kg/day) for 2 days and IMRT-TBI (12 Gy) for 3 days. As suggested by existing literature, additional cytarabine or etoposide administration was at the discretion of the attending physician [ 16–19 ]. Standard GVHD prophylaxis consisted of a calcineurin inhibitor (cyclosporine or tacrolimus) with short-term methotrexate or mycophenolate mofetil.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective cohort study was conducted using a Japanese transplant registry database to compare the prognosis between the medium-dose ETP/CY/TBI (ETP, total 30 to 40 mg/kg) ( n = 376) and CY/TBI ( n = 1178) conditioning regimens in adults with ALL transplanted at CR between January 1 2000 and December 31 2014 [29]. We are pleased with the fact that more than 300 adults with ALL underwent allo HSCT with the medium-dose ETP/CY/TBI conditioning regimen in the almost three years after enrollment in the prospective multi-center phase II clinical trial in Japan was completed.…”
Section: Recent Outcomes Of Medium-dose Etp/ct/tbi and Cy/tbi Condmentioning
confidence: 99%
“…Although the ETP-based regimens (usually 40–70 mg/kg as a single dose) showed efficacy to some extent, severe toxicities were often seen [24]. Among those regimens, the medium-dose (intravenous administration over three hours at a dose of 15 mg/kg once daily for two days) ETP added to a 120 mg/kg CY plus 12 Gy TBI conditioning regimen appears to be promising for allo HSCT in adults aged under 50 years with ALL when transplanted at CR1 and also at CR2, showing an excellent outcome without increasing relapse and transplant-related mortality (TRM) rates [25,26,27,28,29]. In contrast, RIC regimens have also been applied to adults with ALL and favorable outcomes have been obtained; however, relapse and TRM rates remain high [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%